Coexistence of Ankylosing Spondylitis and Löfgren's Syndrome. (10th March 2014) - Kobak, Senol; Sever, Fidan; Sivrikoz, Oya; Karaarslan, Ahmet
Abstract : A 46-year-old male patient diagnosed with ankylosing spondylitis presented to our polyclinic with complaints of pain, swelling, and limitation in joint mobility in both ankles and erythema nodosum skin lesions in both pretibial sites. The sacroiliac joint graphy and the MRI taken revealed active and chronic sacroiliitis. On the thorax CT, multiple mediastinal and hilar lymphadenopathies were reported. Mediastinoscopic excisional lymph node biopsy was taken and noncalcified granulomatous structures, lymphocytes, and histiocytes were determined on histopathological examination. The patients were diagnosed with ankylosing spondylitis, sarcoidosis, and Löfgren's syndrome. NSAIDs, sulfasalazine, and low dose corticosteroid were started. Significant regression was seen in the patient's subjective and laboratory assessments.